BMP and non-canonical Wnt signaling are required for inhibition of secondary tail formation in zebrafish - Yang, Yi (Company of Biologists, 2011)
The role of bone morphogenetic protein (BMP) signaling in specifying cell fate in the zebrafish tailbud has been well established. In addition to a loss of ventral tissues, such as ventral tailfin and cloaca, some embryos with compromised BMP signaling produce an additional phenotype: a ventrally located secondary tail containing both somitic muscle and notochord. This phenotype has been proposed to reflect a fate-patterning defect due to a change in a hypothesized BMP activity gradient. Here, we show that a defect in morphogenetic movements, not fate patterning, underlies the formation of secondary tails in BMP-inhibited embryos. Our data indicate that BMP signaling is activated in the ventroposterior tailbud to promote cell migration during tailbud protrusion, and that defective migration of these cells in BMP mutants ultimately leads to bifurcation of the caudal notochord. Additionally, we show that non-canonical Wnt signaling is also required for proper tail morphogenesis, possibly by maintaining cohesion of notochord progenitors by regulation of cadherin localization. We propose a model in which BMP and the non-canonical Wnt pathway regulate tail morphogenesis by controlling cell migration and cell adhesion within the tailbud.